Interaction of Effect upon Remediating Prospective Science Teachers’ Misconceptions by Guidance Level in Inquiry Teaching with Science Process Skills - Arı, Üzeyir; Peşman, Haki; Baykara, Oktay (Bartin University, 2017)
In inquiry teaching (IT), minimum instructor guidance may interfere with learning, even cause to acquire misconceptions. Therefore, in this study, the level of guidance was increased by using “scaffolding” in the phase of “drawing a conclusion” in IT (Scaffolded Inquiry Teaching - SIT), and their effects on remediating misconceptions were investigated. Science Process Skills (SPS) of the students were identified as “aptitude,” and the effects of the treatments on refining misconceptions were compared for students with low, moderate, and high level of SPS. Thus, this study is an AptitudeTreatment Interaction (ATI) research. Freshman students studying in the department of Science Education at Fırat University in 2015-2016 academic year participated in the study. The students assigned to the groups randomly, and IT was used in the control group while SIT was used in the experimental group. Data were collected by using “Science Process Skills Test” (Pretest) and “Simple Electric Circuits Diagnostic Test” (Posttest). To analyze the data, Johnson-Neyman Technique was used. In conclusion, IT was observed to be more effective than SIT on refining misconceptions of the students with high level of SPS. Nevertheless, for the students with low level of SPS, SIT was observed to be more effective.

Sorgulamaya dayalı öğretim (SDÖ) yönteminde minimum öğretmen rehberliği öğrenmeyi güçleştirebilir; hatta kavram yanılgıları kazanmaya da neden olabilir. Bu nedenle bu çalışmada SDÖ yönteminin “sonuca varma” aşamasında “yapı iskeleleri” kullanarak rehberliğin düzeyi artırılmış (YİSDÖ) ve kavram yanılgılarını gidermedeki etkileri incelenmiştir. Öğrencilerin bilimsel süreç becerileri (BSB) kişisel özellik olarak belirlenmiş; uygulanan yöntemlerin kavram yanılgılarını azaltmadaki etkileri düşük, orta ve yüksek BSB’lere sahip öğrenciler için kıyaslanmıştır. Dolayısıyla bu çalışma bir Kişisel Özellik-Uygulama Etkileşimi (ÖZUYET) araştırmasıdır. Çalışmaya 2015-2016 öğretim yılında Fırat Üniversitesi Fen Bilimleri Öğretmenliği bölümünde okuyan birinci sınıf öğrencileri katılmıştır. Öğrenciler deney ve kontrol grubuna seçkisiz atanmış, kontrol grubunda SDÖ, deney grubundaysa YİSDÖ yöntemi uygulanmıştır. Veriler “Bilimsel Süreç Becerileri Testi” (ön-test) ve “Basit Elektrik Devreleri Tanı Testi” (son-test) kullanılarak toplanmıştır. Verilerin analizindeyse Johnson-Neyman tekniği kullanılmıştır. Sonuç olarak BSB’leri yüksek olan öğrencilerin kavram yanılgılarını azaltmada SDÖ yönteminin YİSDÖ yöntemine kıyasla daha etkili olduğu gözlenmiştir. Ancak BSB’leri düşük olan öğrencilerde, YİSDÖ yönteminin daha etkili olduğu görülmüştür.
Sorgulamaya Dayalı Öğretimde Rehberlik Düzeyinin Bilimsel Süreç Becerileriyle Etkileşimi